2020
DOI: 10.1074/jbc.rev120.013433
|View full text |Cite
|
Sign up to set email alerts
|

Enigmatic MELK: The controversy surrounding its complex role in cancer

Abstract: The Ser/Thr protein kinase MELK (maternal embryonic leucine zipper kinase) has been considered an attractive therapeutic target for managing cancer since 2005. Studies using expression analysis have indicated that MELK expression is higher in numerous cancer cells and tissues than in their normal, nonneoplastic counterparts. Further, RNAi-mediated MELK depletion impairs proliferation of multiple cancers, including triple-negative breast cancer (TNBC), and these growth defects can be rescued with exogenous WT M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…Applying the GOT-IT (Guidelines On Target Assessment for Innovative Therapeutics) framework by analysing causality more stringently (critical path question (CPQ) #1: ‘Is the target perturbation a cause or consequence of the human disease process?’) and by focusing on controlling tool compound and small interfering RNA quality (Box 3 ) could have helped to identify the target’s non-essential nature for cancer cell proliferation early on and could have directed the OTS167 programme to address the poor selectivity for MELK before progressing into expensive clinical proof-of-concept studies 183 .…”
mentioning
confidence: 99%
“…Applying the GOT-IT (Guidelines On Target Assessment for Innovative Therapeutics) framework by analysing causality more stringently (critical path question (CPQ) #1: ‘Is the target perturbation a cause or consequence of the human disease process?’) and by focusing on controlling tool compound and small interfering RNA quality (Box 3 ) could have helped to identify the target’s non-essential nature for cancer cell proliferation early on and could have directed the OTS167 programme to address the poor selectivity for MELK before progressing into expensive clinical proof-of-concept studies 183 .…”
mentioning
confidence: 99%
“…MELK is a member of the snf1/AMPK family of protein serine/threonine kinases and highly associated with accelerated proliferation of cancer stem cells (CSC) in various organs (Ganguly et al, 2014). It has been considered to be a potential therapeutic target in cancer since 2005 (McDonald and Graves, 2020). Previous research has showed that MELK has the ability of inhibition of different cell cycle occurred in BC cells (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that MELK is upregulated under cell cycle dependency in various cancers, including breast cancer, even though CRISPR/Cas9-mediated MELK knockout has no effect on cancer cell proliferation. In this regard, McDonald IM and Graves LM mentioned in their review the possibility that MELK is functionally redundant for a specific cell cycle pathway, such that MELK is not indispensable for the cell cycle in normal cells but is necessary for specific conditions in cancer cells [ 69 ]. On the other hand, CRISPR/Cas9-mediated MELK knockout may allow for compensatory signaling networks as MELK functional redundancy, whereas RNAi-mediated MELK knockdown does not allow for the possible redundant pathway [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, McDonald IM and Graves LM mentioned in their review the possibility that MELK is functionally redundant for a specific cell cycle pathway, such that MELK is not indispensable for the cell cycle in normal cells but is necessary for specific conditions in cancer cells [ 69 ]. On the other hand, CRISPR/Cas9-mediated MELK knockout may allow for compensatory signaling networks as MELK functional redundancy, whereas RNAi-mediated MELK knockdown does not allow for the possible redundant pathway [ 69 ]. Collectively, despite strong controversy, these findings suggest that MELK is necessary for the growth of cancer cells, especially breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%